Decoupling economic and energy growth: aspiration or reality?. (16th March 2021) - Guo, Jin; Li, Chuan-Zhong; Wei, Chu
Abstract: Energy has long been a driving force of economic growth; however, it comes with environmental costs and security challenges. This study analyzes the energy–economy nexus and explores their decoupling possibilities by using cross-country data over the years 1971–2014. The results indicate that, while energy use and economic growth exhibit a typical inverted U-shaped decoupling relationship for the industrialized countries, they have been rising in tandem for the developing economies. Among factors, it is the economic scale, population size, and energy intensity that are the decisive factors. Among countries, it is the U.S., China, and India, which mainly dominate the global economy–energy trend. Overall, we conclude that any global economy–energy decoupling may confront challenges and uncertainty. To better decouple economic growth from energy use, we propose policies for more structural reforms, a clean energy system, improved energy efficiency, and efficient energy demand-side management.